Ethnobotanical study of medicinal plants of Resunga hill used by Magar community of Badagaun VDC, Gulmi district, Nepal - Acharya, Rajendra (Scientific World, 2012)
Present study aims to explore the ethnobotanical information on medicinal plants used by Magar community of Badagaun VDC of Gulmi district. The study was carried out during different periods of the year 2010. Informations on plant and plant parts uses were collected interviewing key informants by using semi-structured open-ended questionnaire. Altogether 161 different plant species belonging to 87 familes and 144 genera were documented and majority of them are herbs. In terms of plant parts use, leaf and stem/bark are in top priorities. These plants are used to treat different ailments ranging from gastro-intestinal to headache and fever, respiratory tract related problems to dermatological problems, snake bite to ophthalmic and cuts and wounds. Easy access to modern medicines and less recognition of traditional healers are the main causes leading to decrease in interest of young generation in the use of traditional medicinal practices. Scientific World, Vol. 10, No. 10, July 2012 p54-65 DOI: http://dx.doi.org/10.3126/sw.v10i10.6863